Looking for Social Work Values and Ethics in the Textbooks of Social Services Administration Over the Past 50 Years (1965–2014). Issue 2 (15th March 2017) - Pak, Chui-Man; Cheung, Johnson Chun-Sing; Tsui, Ming-Sum
ABSTRACT: This article presents the findings of a review of 40 social services administration textbooks published between 1965 and 2014 to examine their coverage of social work values and ethics and the preparation of administrators for practice in a value-based profession. The coverage of values and ethics in these texts varied considerably and close to one third paid little or no attention to the ethical precepts of the social work profession. Textbook authors and editors are advised to take a more proactive stance in encouraging social work administrators to reconsider the management of human services from a value-laden point of view.